Rates of return to schooling and the quality of education in England and Wales - David Campbell (University of Kent, Department of Economics, 2001)
Raising the quality of education has been one of the main objectives of the current government in Britain. By devoting more resources to the education sector, it is expected that pupils will achieve higher educational attainment by the time their years of compulsory schooling ends. This study attempts to assess the effect that the quality of schooling has on the subsequent labour market outcomes of a cohort of individuals who received their secondary education in the 1970s. In the first stage of the statistical analysis, an earnings equation is estimated for those in employment at age 33 which produces an estimate of the return to schooling for each local education authority (LEA) in England and Wales. It is found that the return to schooling varies across LEAs, ranging from 6% to 18%. For the second part of the analysis, these LEA-specific returns are regressed on variables capturing the mean level of school quality in each LEA. The results provide little evidence that measures of quality, such as the pupil-teacher ratio, influence the return received for each year of schooling. Some evidence is found, however, that segregating pupils according to ability is beneficial on average since the greatest returns to schooling are observed in LEAs offering selective schools.
Keywords: C23; J31; J24; I21; 330; wage level; returns to education; school quality; Allgemeinbildende Schule; Dienstleistungsqualität; Bildungsniveau; Bildungsertrag; England; Wales